Discursos e práticas na formação de profissionais fisioterapeutas: a realidade dos cursos de fisioterapia na região nordeste do Brasil - Araújo, Francisca Rêgo Oliveira de (2009)
This study had a multidisciplinary focus, investigating the areas of health and education, and proposes to discuss the formation of health professionals, requiring their understanding of the factors involved in the production of knowledge, given that this formation has an impact on the quality of human and social life. The aim of this work was to investigate the relationship existing between the process of physical therapist formation and the practical activities developed during the undergraduate course in the Northeast of Brazil. This is an exploratory descriptive study with qualitative significance. The sample consisted of 73 subjects (33 professors and 40 students) from 6 physical therapy courses at different institutions in the Northeast of Brazil. Data collection was conducted through focus group interviews. In addition, we used a school assessment instrument from the health area. The data, analyzed using dialectical hermeneutics, showed that the Northeast of Brazil has the second largest number of physical therapy courses in the country, with 93 (11 public and 82 private) out of a total of 510. These numbers represent a growth of 1062.5% since 1991. The pedagogical projects are guided by National Curricular Directives as well as by the country s health system. The prevalent pedagogy is that of transmission, and the contents/disciplines are generally not integrated with practice, a situation that hinders the integrality and interdisciplinarity of health care. It can be concluded that there is a need for implementing integrated curricula and for better qualified professors to effectively put this process into practice